Nontoxigenic Vibrio cholerae Non-O1/O139 Isolate from a Case of Human Gastroenteritis in the U.S. Gulf Coast - Hasan, Nur A. (J Clin Microbiol, 2014)
An occurrence of Vibrio cholerae non-O1/O139 gastroenteritis in the U.S. Gulf Coast is reported here. Genomic analysis revealed that the isolate lacked known virulence factors associated with the clinical outcome of a V. cholerae infection but did contain putative genomic islands and other accessory virulence factors. Many of these factors are widespread among environmental strains of V. cholerae, suggesting that there might be additional virulence factors in non-O1/O139 V. cholerae yet to be determined. Phylogenetic analysis revealed that the isolate belonged to a phyletic lineage of environmental V. cholerae isolates associated with sporadic cases of gastroenteritis in the Western Hemisphere, suggesting a need to monitor non-O1/O139 V. cholerae in the interest of public health.